Collision in the boardroom: Director skill interdependence and corporate entrepreneurship in technology‐intensive firms - Pavićević, Stevo; Keil, Thomas; Zahra, Shaker A. (Strategic Management Journal, 2026)
Abstract Research Summary Board human capital theory posits that directors' skills shape firm behavior. Most studies, however, examine one skill type at a time, assuming that each director contributes independently of the other skills represented on the board. We introduce the concept of director skill interdependence , theorizing that a director's influence depends on the skills of fellow directors and their committee assignments. Focusing on entrepreneurial directors in technology‐intensive firms, we find that they increase resource allocation toward corporate entrepreneurship (CE); however, this effect diminishes as the number of finance‐skilled directors increases, whether on the board or on its corporate development committee. These findings challenge the view of directors' skills as isolated inputs. Instead, the effects of directors' skills are contingent on the board's skill composition and committee structure. Managerial Summary In technology‐intensive firms, directors with entrepreneurial skills are often expected to stimulate corporate entrepreneurship (CE). Our findings suggest this relationship is less straightforward. While entrepreneurial directors do increase investment in CE, their impact weakens when directors with finance skills are prevalent on the board or its corporate development committee. These results underscore the importance of director skill interdependence —the idea that a director's influence depends on the skills and roles of fellow directors. Boards should therefore consider not only who is appointed, but also how directors' skills align with one another and how those skills are deployed through committee assignments. Preventing the dominance of conflicting skill sets may enhance the board's ability to support innovation, venturing, and long‐term strategic renewal.